2009
DOI: 10.1016/j.yjmcc.2009.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular superoxide dismutase regulates cardiac function and fibrosis

Abstract: Aims-Extracellular superoxide dismutase (EC-SOD) is an antioxidant that protects the heart from ischemia and the lung from inflammation and fibrosis. The role of cardiac EC-SOD under normal conditions and injury remains unclear. Cardiac toxicity, a common side effect of doxorubicin, involves oxidative stress. We hypothesize that EC-SOD is critical for normal cardiac function and protects the heart from oxidant-induced fibrosis and loss of function.Methods-C57BL/6 and EC-SOD-null mice were treated with doxorubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 50 publications
(58 reference statements)
1
36
0
Order By: Relevance
“…EcSOD-mediated protection against cardiac toxicity has been shown by Kliment et al where EcSOD global knockout mice showed exacerbated cardiac dysfunction, myocardial apoptosis and fibrosis following doxorubicin injection 41 . We have previously shown that adenovirus-mediated gene transfer of EcSOD in the heart elicits protective effects on cardiac function following myocardial infarction in rabbits 42 .…”
Section: Discussionmentioning
confidence: 96%
“…EcSOD-mediated protection against cardiac toxicity has been shown by Kliment et al where EcSOD global knockout mice showed exacerbated cardiac dysfunction, myocardial apoptosis and fibrosis following doxorubicin injection 41 . We have previously shown that adenovirus-mediated gene transfer of EcSOD in the heart elicits protective effects on cardiac function following myocardial infarction in rabbits 42 .…”
Section: Discussionmentioning
confidence: 96%
“…This assay was adapted from previously reported methods and used to quantify collagen content (20). Briefly, hearts from 3 and 6 mo posttreatment DM2 and age-matched control mice were dried in glass containers for 48 h at 100°C.…”
Section: Methodsmentioning
confidence: 99%
“…Together, these antioxidant compounds maintain reactive species at nanomolar levels, preventing the disruption of redox homeostasis. SOD, responsible for the dismutation of O ÅÀ 2 to H 2 O 2 , plays a key role in the redox homeostasis under both physiological and pathological conditions (Kliment et al, 2009;Miriyala et al, 2012). This family of ubiquitous enzymes contains two main isoforms: MnSOD (manganese superoxide dismutase, located in the mitochondrial matrix) and Cu-ZnSOD (copper-zinc superoxide dismutase, located in the cytosol, extracellular space and mitochondrial inter membrane space).…”
Section: Antioxidant Systemsmentioning
confidence: 99%